Asimilasi dan Akulturasi Penyembahan Baal di Bangsa Israel: Pendekatan Sosio Teologis menurut Teori Multi Stage Assimilation Milton M. Gordon - Gandi Wibowo (LPPM STT Baptis Kalvari, 2021)
The excellence of Israel as God's chosen nation does not make the hearts of this nation attached to and obey God. Israel in Old Testament times found it difficult to break away from the idolatry of Baal worship. Until the end of the Kingdoms of Northern and Southern Israel, accompanied by the Babylonian exile, this foreign god-worshiping practice gradually declined drastically. Understanding this phenomenon in a normative theological context usually sees Baal worship as a sin that just arises without seeing the process of assimilation and acculturation of Israeli beliefs. But a socio-theological approach will make the understanding of the phenomenon of Baal worship in Ancient Israel clearer. Baal as the god of fertility of the Canaanites was widely known to Ancient Egypt, especially in the north. The adoption of Baal as a fertility god had a political aspect for Ancient Egyptians to build alliances with surrounding nations, apart from the spiritual aspect of the polytheism they built. Israel's slavery in Egypt influenced the mindset of Israelis and their behavioral tendency to compromise the worship of foreign gods. The strength of foreign culture entered Israel due to the gradual assimilation process from marriage to the climax of becoming the national god of the Israelites in Ahab's day.